Crystallographic analysis of archaeal ribosomal protein L11. Issue 8 (1st August 2015) - Mitroshin, Ivan; Garber, Maria; Gabdulkhakov, Azat
<x xml:space="preserve">Abstract</x> Ribosomal protein L11 is an important part of the GTPase‐associated centre in ribosomes of all organisms. L11 is a highly conserved two‐domain ribosomal protein. The C‐terminal domain of L11 is an RNA‐binding domain that binds to a fragment of 23S rRNA and stabilizes its structure. The complex between L11 and 23S rRNA is involved in the GTPase activity of the translation elongation and release factors. Bacterial and archaeal L11–rRNA complexes are targets for peptide antibiotics of the thiazole class. To date, there is no complete structure of archaeal L11 owing to the mobility of the N‐terminal domain of the protein. Here, the crystallization and X‐ray analysis of the ribosomal protein L11 from Methanococcus jannaschii are reported. Crystals of the native protein and its selenomethionine derivative belonged to the orthorhombic space group I222 and were suitable for structural studies. Native and single‐wavelength anomalous dispersion data sets have been collected and determination of the structure is in progress.